Digital pathways to healthier diets: How Uganda’s agri-food MSMEs are reshaping food systems - Kikulwe, Enoch; Ajambo, Susan; Birachi, Eliud; Ogutu, Sylvester; Chege, Christine (2025)
Micro, small, and medium enterprises (MSMEs) are emerging as powerful drivers of food systems transformation in Uganda. Through digital innovation, these enterprises are addressing persistent bottlenecks in agricultural value chains, making it easier for farmers to access quality inputs, receive expert advice, and deliver nutritious foods to markets efficiently.